Preliminary exploration of nursing care safety indices in Hellenic critical care units - Kostaki, Dimitra; Karanikola, Maria (My University, 2007)
Background: In intensive care units (ICUs), the majority of patient care tasks are directly performed by nurses. Therefore, nurses bear the responsibility of preventing errors and adverse events during patient care delivery. Purpose: We explored a) the degree of nursing care delivery safety in Hellenic ICUs, by quantification of an array of critical nursing situations, and b) potential associations between safety of care indices and patients' characteristics, organizational parameters, staffing, and nurses' work adjustment characteristics. Method: This was a descriptive correlational study with cross-sectional comparisons. A combination of convenience and random sampling was employed. The study was carried out at two public and two private sector ICUs in Athens. 65 ICU patients and 19 nurses were included, The modified Critical Nursing Situation Index, TISS-28, APACHE-II, the Index of Work Satisfaction, the Maslach Burnout Inventory, and Berger's self-esteem scale were employed.
Keywords: Intensive care units; Nurses; Burnout